Price Discrimination in Online Retail - Christoph Michael Hindermann (ZBW – Leibniz Information Centre for Economics, 2018)
Although newspapers and online blogs provide a variety of anecdotal evidence for price discrimination, they are mostly not based on a scientific and systematic approach. This survey gives a short overview of scientific price discrimination studies in online retail. At first, it contains a short methodological part which shows how price discrimination can be detected. Thereafter, the results of different price discrimination studies are presented, showing that the prevalence of price discrimination varies across studies. Studies who analyze only `popular' websites find a higher rate of prevalence than studies focusing also on `unpopular' websites. As far as scientific evidence is available, online prices hinge on user-based, technical, and location-based features. The dispersion of the price seems to be largest when firms discriminate between users from different countries. Finally, potential reasons why price discrimination is not applied by all retailers are given.
Keywords: D40; M20; 330; Price Discrimination; Online Retail; Price Differentiation; Pricing